PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KECAP MANIS MEREK BANGO - Stanlie, Irvan (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2018)
From the analysis using multiple linear regression method, the obtained results thatvariable of price has a significant impact on buying decision with result t-test (partial) obtained tvalue > t table (3.693 >1.993) with significant obtained about 0.000 < 0.05 then Ho rejected and Haaccepted. Variable of product quality has a significant impact on buying decision with result t-test(partial) obtained t value > t table (2.787 >1.993) with significant value obtained about 0.007 < 0.05then Ho rejected and Ha accepted. Variable of brand image has a significant impact on buyingdecision with result t-test (partial) obtained t value > t table (2.289 >1.993) with significant valueobtained about 0.025 < 0.05, then Ho rejected and Ha accepted. Variable of price, product quality,and brand image that simultaneous has a significant impact on buying decision with result F-test(simultaneous) obtained F value > F table (17.126 > 2.730) with significant value obtained about0.000 < 0.05 then Ho rejected and Ha accepted. Dimensions Coefficient of determination about0.389 or 38.9% which means independent variables consisting of price, product quality, and brandimage has a contribution obtained 38.9% toward buying decision, while the remaining (100% -38.9% = 61.1%) was influenced by factors other factors that are not discussed in this study.